Insight on compatibilization of LLDPE/PS blends from morphology, interfacial state, mechanical properties and melt properties: Comb-like copolymer vs diblock copolymer. (18th March 2021) - Wang, Yanhui; Zhang, Shaofeng; Jiang, Hanqing; Lin, Yichao; Xing, Haiping; Tang, Tao
Abstract: The influence of the composition and chain architecture of compatibilizers on the compatibilization efficiency in immiscible LLDPE/PS blends was studied. Firstly, the compatibilization provided by ethylene-styrene diblock copolymer (PS- b -PE) and comb-like copolymers (PS- cb -PE) was compared from the morphology, interfacial state, mechanical properties and melt properties of the blends. Compared to PS- b -PE as a compatibilizer in LLDPE/PS blends, depending on the side chain composition and side chain density of PS- cb -PE copolymers (PS as backbone), the comb-like copolymers showed a poor compatibilization in the cases with PE as side chains, especially in the case with high grafting density, but a much better compatibilization in the cases with PS- b -PE (PS- cb -(PS- b -PE)) or heterografted PS/PE chains as side chains (PS- cb -(PS/PE)). It could be seen that the chain architecture of the compatibilizers played a key role in the compatibilization efficiency of LLDPE/PS blends. Furthermore the compatibilization of these comb-like copolymers dramatically improved the CO2 foaming capacity of the LLDPE/PS blends, which is ascribed to significant effect of the compatibilization on the increased interfacial interaction and rheological response of the blends, such as the improved strain-hardening behavior of the compatibilized blends. Graphical abstract: Image 1 Highlights: The chain architecture of compatibilizers shows a strong effect on the compatibilization efficiency in LLDPE/PS blends. The comb-like copolymers with certain composition presents a better compatibilization on LLDPE/PS blends. The compatibilization of comb-like copolymers dramatically improved the CO2 foaming capacity of LLDPE/PS blends.